Assessing Galala City as Infra Habitation: Gaps, Challenges and Opportunities for Sustainable Human Settlements - Mahgoub, Yasser (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2026)
This study evaluates Galala City as a contemporary example of Infra Habitation, focusing on how its infrastructure supports sustainable and resilient human settlement. Using established assessment tools—including the InVEST Habitat Quality Model, Habitat Suitability Modelling, the Habitat Hectare Method, rapid assessment protocols, and the Disaster Habitation Model—the research develops a tailored Infra Habitation framework for Galala. Findings show that while the city exhibits strong engineered infrastructure, including highways, tunnels, and a desalination-based water system, significant gaps persist in ecological integration, mixed-use development, public transit, and social services. The analysis highlights weaknesses in walkability, housing diversity, vegetation cover, and long term livability. A preliminary Infra Habitation scorecard identifies priority areas for improvement, particularly in environmental restoration, neighborhood planning, and mobility systems. The study concludes by proposing strategic actions to guide Galala’s evolution into a more inclusive, ecologically responsive, and human-centered city aligned with UN-Habitat principles.